Projetos para produção de residências unifamiliares em light steel framing - Vivan, André Luiz (Universidade Federal de São Carlos, 2011)
This work has the aim to propose guidelines for the preparation of designs for production with the construction of single family houses of Light Steel Framing. These guidelines involve considerations about the presentation of designs and assembly sequences on the main elements of a building in Light Steel Framing, promoting higher constructability on projects. Parallel to these guidelines were developed some graphical detail, with respect to the elements discussed, based on the concept of Design for Assembly. For this, have been used the information from the literature review, which deals with concepts such as Concurrent Engineering, Lean Design and Design for Production, and information gathered in structured interviews. The product of this work contributes to the advancement of studies about the design process of Light Steel Framing, besides promoting the use of concepts just discussed or used in Construction. Being a prefabricated building system, Light Steel Framing collaborates with the modernization of the processes involved in small works and facilitates the use of management principles such as Lean Construction and tools such as Design for Assembly.
Keywords: Administração de produto; Projeto para produção; Light steel framing; Construção enxuta; Design for production; Light steel framing; Lean Construction; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL